Self-assertiveness of the right of obtaining Administrative Documents - Comparative analytical study - Zangna, Esmael Najmadin; Jabar, Muhsin Jalal (Journal of Legal and Political Studies, 2020)
The right of access to administrative documents is recognized in the international and domestic legal system. It has become one of the fundamental concepts required to achieve the principle of transparency, which is also becoming one of the basic tapes that predict and indicate the existence of good governance in any country. The right of the study has its own subject, in a manner that distinguishes it from the right to obtain information, although there are characteristics that combine the two rights, but there are distinct characteristics that account for and is characterized by the right to obtain administrative documents without information. However, there is a problem following the exercise of this right in the lack of clarity of legal controls, especially in terms of its concept and content, due to the emergence of confusion between the concepts of the right to information and the right to obtain administrative documents, in addition to the lack of legal awareness by citizens About this right and its constitutional and legal guarantees. Therefore, this research aimed to define the concept of "the right to obtain administrative documents" with some precision, to form an attempt to enrich the jurisprudence of Iraqi and Kurdistan and the public in general, and to form a basis for researchers and concerned with this subject, on the one hand. To the best legal organization, to ensure the proper implementation of this constitutional and legal right, on the other. The research also attempted to achieve its objectives and address its research problem by dividing the study into two subjects, one devoted to explain the characteristics of the right to obtain administrative documents. and another research to determine the meaning, elements and nature of this right.Until he reached his conclusion of the most important conclusions and recommendations.
Keywords: right of access to administrative documents; domestic legal system; legal organization; good governance; fundamental concepts